2012
DOI: 10.1007/s10803-012-1711-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Effect of Spatial Complexity on Visual Short-Term Memory and Self-Reported Autistic-Like Traits in Typically Developed Individuals

Abstract: This report examines effects of the spatial complexity of configurations on visual short-term memory (VSTM) capacity for individuals from the general population differing on autism-spectrum quotient (AQ) scores. During each trial, nine-line segments with various orientations were arrayed in simple or complex configurations and presented in both memory and test displays. Typically, VSTM capacity decreases with increasing configuration complexity. We found that VSTM capacity for simple configurations was larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been shown that the autism characteristics can be identified in the general population (Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001). Thus, it is possible that people with a high-autism-quotient would also differ in this task compared to people with a low-autism-quotient, as was found in other studies using different tasks (e.g., Richmond, Thorpe, Berryhill, Klugman, & Olson, 2013;Takahashi, Gyoba, & Yamawaki, 2013).…”
Section: Discussionmentioning
confidence: 74%
“…It has been shown that the autism characteristics can be identified in the general population (Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001). Thus, it is possible that people with a high-autism-quotient would also differ in this task compared to people with a low-autism-quotient, as was found in other studies using different tasks (e.g., Richmond, Thorpe, Berryhill, Klugman, & Olson, 2013;Takahashi, Gyoba, & Yamawaki, 2013).…”
Section: Discussionmentioning
confidence: 74%